Circulating and disseminated tumor cells from breast cancer patient-derived xenograft-bearing mice as a novel model to study metastasis. Issue 1 (December 2015) - Giuliano, Mario; Herrera, Sabrina; Christiny, Pavel; Shaw, Chad; Creighton, Chad; Mitchell, Tamika; Bhat, Raksha; Zhang, Xiaomei; Mao, Sufeng; Dobrolecki, Lacey; Al-rawi, Ahmed; Chen, Fengju; et al.
Abstract Introduction Real-time monitoring of biologic changes in tumors may be possible by investigating the transitional cells such as circulating tumor cells (CTCs) and disseminated tumor cells in bone marrow (BM-DTCs). However, the small numbers of CTCs and the limited access to bone marrow aspirates in cancer patients pose major hurdles. The goal of this study was to determine whether breast cancer (BC) patient-derived xenograft (PDX) mice could provide a constant and renewable source of CTCs and BM-DTCs, thereby representing a unique system for the study of metastatic processes. Methods CTCs and BM-DTCs, isolated from BC PDX-bearing mice, were identified by immunostaining for human pan-cytokeratin and nuclear counterstaining of red blood cell-lysed blood and bone marrow fractions, respectively. The rate of lung metastases (LM) was previously reported in these lines. Associations between the presence of CTCs, BM-DTCs, and LM were assessed by the Fisher's Exact and Cochran-Mantel-Haenszel tests. Two separate genetic signatures associated with the presence of CTC clusters and with lung metastatic potential were computed by using the expression arrays of primary tumors from different PDX lines and subsequently overlapped to identify common genes. Results In total, 18 BC PDX lines were evaluated. CTCs and BM-DTCs, present as either single cells or clusters, were detected in 83% (15 of 18) and 62.5% (10 to16) of the lines, respectively. A positive association was noted between the presence of CTCs and BM-DTCs within the same mice. LM was previously found in 9 of 18 (50%) lines, of which all nine had detectable CTCs. The presence of LM was strongly associated with the detection of CTC clusters but not with individual cells or detection of BM-DTCs. Overlapping of the two genetic signatures of the primary PDX tumors associated with the presence of CTC clusters and with lung metastatic potential identified four genes (HLA-DP1A, GJA1, PEG3, andXIST ). This four-gene profile predicted distant metastases-free survival in publicly available datasets of early BC patients. Conclusion This study suggests that CTCs and BM-DTCs detected in BC PDX-bearing mice may represent a valuable and unique preclinical model for investigating the role of these rare cells in tumor metastases.